2021
DOI: 10.3390/s21124214
|View full text |Cite
|
Sign up to set email alerts
|

Deployment, Calibration, and Cross-Validation of Low-Cost Electrochemical Sensors for Carbon Monoxide, Nitrogen Oxides, and Ozone for an Epidemiological Study

Abstract: We designed and built a network of monitors for ambient air pollution equipped with low-cost gas sensors to be used to supplement regulatory agency monitoring for exposure assessment within a large epidemiological study. This paper describes the development of a series of hourly and daily field calibration models for Alphasense sensors for carbon monoxide (CO; CO-B4), nitric oxide (NO; NO-B4), nitrogen dioxide (NO2; NO2-B43F), and oxidizing gases (OX-B431)—which refers to ozone (O3) and NO2. The monitor networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 42 publications
0
25
0
3
Order By: Relevance
“…When the sensors were evaluated prior to deployment in January 2019 in chamber testing, the NO 2 sensor did not exhibit a response to O 3 . It has also been shown that as the NO 2 sensor ages, the built-in O 3 scrubber can degrade, resulting in an increasing cross-sensitivity to O 3 and reduced sensor accuracy, and others have seen variations in the efficacy of the ozone scrubber, including ozone breakthrough and filter aging. , Thus, we considered in our model the possibility of continued cross-sensitivity of the NO 2 sensor to ozone.…”
Section: Resultsmentioning
confidence: 99%
“…When the sensors were evaluated prior to deployment in January 2019 in chamber testing, the NO 2 sensor did not exhibit a response to O 3 . It has also been shown that as the NO 2 sensor ages, the built-in O 3 scrubber can degrade, resulting in an increasing cross-sensitivity to O 3 and reduced sensor accuracy, and others have seen variations in the efficacy of the ozone scrubber, including ozone breakthrough and filter aging. , Thus, we considered in our model the possibility of continued cross-sensitivity of the NO 2 sensor to ozone.…”
Section: Resultsmentioning
confidence: 99%
“…For example, NGMSs cannot be applied as reference-grade instrumentation in monitoring exposure to airborne chemicals for regulatory purposes [8]. NGMSs should be used paired with traditional methods for a period to allow the hygienist to calibrate the sensors in the most efficient way to obtain significant data for the risk assessment [29][30][31]. Another relevant issue regards power supply, in fact, most NGMSs cannot run for many hours without recharging [8].…”
Section: Problem Statementmentioning
confidence: 99%
“…Additionally, the devices are equipped with sensors to measure ambient variables like: temperature ( • C), relative humidity (%), ultraviolet radiation (UV), ambient noise (dB), and atmospheric pressure (hPa). For gas sensing, electrochemical sensors from Alphasense (Zuidema et al, 2021) were used. The sensor outputs an analog signal, which is digitized with the help of an 18-bit ADC.…”
Section: Low-cost Air Quality Sensing Devices (Qhawaxs)mentioning
confidence: 99%